RESULTS OF THE USE OF MINIMALLY INVASIVE TECHNOLOGIES IN THE SURGICAL TREATMENT OF HEPATIC ECHINOCOCCOSIS AND ITS COMPLICATIONS - K.M. KURBONOV; Z.A. AZIZZODA; M.G. EFANOV; K.R. RUZIBOYZODA (Avicenna Tajik State Medical University, 2020)
Objective: To evaluate the results of using minimally invasive technologies in the surgical treatment of hepatic echinococcosis (HE) and its complications. Methods: The results of examination and surgical treatment of 165 patients with HE and its complications using minimally invasive technologies are presented. Results: 77 patients with uncomplicated HE underwent: open echinococcectomy (EE) from various mini-accesses (n=37), laparoscopic EE (n=30), PAIR technology (n=6), hepatic resection using the da Vinci S robotic complex (n=4). In patients with suppurated hydatid cysts (n=49) a combination of percutaneous cyst puncture with laparoscopic (4) and open (5) EE; PAIR technology (5) and laparoscopic EE (35) were performed. All 39 patients with intrabiliary rupture of hydatid cysts underwent two-stage interventions: percutaneous transhepatic choledochostomy followed by laparoscopic (7) and traditional (4) EE; endoscopic papillosphincterotomy (EPST) followed by open EE (9); laparoscopic choledochostomy followed by open EE (3); EPST followed by laparoscopic total (2) and subtotal (14) pericystectomy. Postoperative complications were noted in 29 (17.5%), relapses of the disease - in 12 (10.9%), lethal outcome - in 1 (0.6%) cases. Based on the analysis of the study, an algorithm for choosing the method of surgical treatment for HE and its complications was developed. Conclusion: The use of minimally invasive technology for hepatic echinococcosis can improve surgical treatment outcomes.